Computing Minimum Support Price to Promote Agriculture as a Sustainable Model - P.Harikumar, K.P.K. Devan (International Journal of Advanced Science and Technology, 2019)
In a world where every business sector is thriving to prove its place and move to larger revenue streams, the plight of Indian farmers still remain in trying to make the bare ends meet. With a loosely coupled system of farming practices and an even more aloof mindset of treating agriculturalists, the world might be led into a future where food becomes luxury only for the super rich. Even though the Indian government has tried to take a lot of measures to help agriculturalists from the clutches of private contractors, the Minimum Support Price (MSP) set by the government is not profitable. The downfall of produce or the market demand might be a cause of poor distribution across the area or due to a climatic drift which might have caused a dip in the cultivation of crops. Even after a lot of such constraints being studied by the government in collaboration with various agricultural groups, MSP still falls short of the farmer’s requirements. Using Machine Learning, specifically SVM classifiers and cross validation, the proposed system suggests the most profitable crops that can be cultivated in that particular region and the predicted selling price i.e., MSP of the produce. Hence, the idea will create a win-win situation for the farmer as well as the government wherein the farmer will be aware of his production and the rate at which he must sell it to sustain in his occupation.